Sports practices and leisure in the “Periférico Oriente linear park” in Iztapalapa, Mexico City, 2020-2022 (2024)
Sports practices and leisure are necessary elements for socialization and the physical and emotional well-being of people, especially in large Latin American cities where public spaces dedicated to carrying out these activities are increasingly scarce and insufficient in the face of growth. urban. Therefore, this research analyses the sports and leisure practices that are presented in the Periférico Oriente linear park after its renovation, as well as the infrastructure of the place to know if it responds to the needs of the  population or not, and if the park is a space for recreation, meeting and social integration. To do this, direct observation was used as an ethnographic method, which allowed us to investigate the different uses and forms of appropriation that the different users make of the park, and surveys were carried out on the users and semi-structured interviews with the instructors of the sports practices. In both instruments, the following items were addressed: general data, safety, equipment and maintenance of the park, uses, sports and leisure practices, and what the park represents. It was identified that the renovation of the linear park has allowed an appropriation of the place through new sports practices such as calisthenics, aerial dance, skating and soccer, and other recreational and leisure activities such as walks, children’s games, rest, coexistence, cinema, music and workshops. All of this has had an impact on the lives of the people who are part of that space.